2006
DOI: 10.2174/157339606778019684
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Arterial Hypertension: Insights from Pediatric Studies

Abstract: Blood pressure is the direct product of cardiac output and total peripheral resistance. Cardiac output is regulated by preload, myocardium contractility and heart rate, while total peripheral resistance depends on afterload and vessel elasticity. The maintenance of blood pressure within normal limits is influenced by neural, humoral and local control mechanisms, which have extensive and complex interactions, making difficult an individual analysis. Thus, isolated or combined disarrangements in these mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 157 publications
(212 reference statements)
0
4
0
Order By: Relevance
“…Alterations in the synthesis and degradation of endothelial factors have recently been described as a contributor to the beginning or maintenance of a series of complications, including changes in vascular reactivity, blood fl ow, and tissue perfusion, which are all present in diabetes, renal diseases, heart failure, and hypertension (Kang et al 2002;Simões e Silva et al 2006c;Nakagawa et al 2007). Recently, studies have shown the presence of reduced levels of Ang-(1-7) in pregnancy complicated by pre-eclampsia (Merril et al 2002) and gestational diabetes (Nogueira et al 2007), corroborating to the hypothesis that changes in circulating levels of Ang-(1-7) can be a marker of a new onset endothelial dysfunction.…”
Section: Winkelmann Et Al 1999mentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the synthesis and degradation of endothelial factors have recently been described as a contributor to the beginning or maintenance of a series of complications, including changes in vascular reactivity, blood fl ow, and tissue perfusion, which are all present in diabetes, renal diseases, heart failure, and hypertension (Kang et al 2002;Simões e Silva et al 2006c;Nakagawa et al 2007). Recently, studies have shown the presence of reduced levels of Ang-(1-7) in pregnancy complicated by pre-eclampsia (Merril et al 2002) and gestational diabetes (Nogueira et al 2007), corroborating to the hypothesis that changes in circulating levels of Ang-(1-7) can be a marker of a new onset endothelial dysfunction.…”
Section: Winkelmann Et Al 1999mentioning
confidence: 99%
“…Most evidence supports a counter-regulatory role for Ang-(1-7) by opposing many Ang II-AT 1 receptor-mediated actions, especially vasoconstriction and proliferation (Simões e Silva et al 2006a; Santos and Ferreira 2007;Chappell 2007). Furthermore, Ang-(1-7) has been associated to the physiopathology of several diseases such as hypertension (Luque et al 1996;Ferrario et al 1998;Simões e Silva et al 2004, 2006b, 2006c, pre-eclampsia (Merril et al 2002;Brosnihan et al 2004;Shah 2005), hypertrophic myocardial disease and congestive heart failure, myocardial infarct (Zisman et al 2003;Santos and Ferreira 2005), chronic renal diseases (Simões e Silva et al 2006b), hepatic cirrhosis (Paizis et al 2005;Pereira et al 2007;Herath et al 2007;Warner et al 2007), diabetic nephropathy (Carey and Siragy 2003b;Tikelis et al 2003;Kalantrina and Okusa 2006), and gestational diabetes (Nogueira et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies show that although the prevalence of primary HTN increases with age, kidney diseases are still in the first line and the diagnostics of HTN in the pediatric population should always take into account the renal perspective. The early diagnosis of secondary HTN in younger children seems of paramount importance, mainly due to the subsequent end-organ damage that may develop during the course of the disease, despite the initially asymptomatic or non-specific clinical picture [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Since Ang (1-7) possesses anti-arrhythmogenic, antithrombogenic, growth-inhibitory and vasoconstriction inhibitory properties, it can be considered as a protective and key counter-regulatory component of the RAAS cascade [75,82,83]. These beneficial effects of Ang (1-7) on the pathology of multiple diseases such as hypertension [77,78,80,84] and diabetic nephropathy [85][86][87][88] have only recently been discovered, opening new possibilities for further drug development.…”
Section: Q4mentioning
confidence: 99%